Joseph Alphonse Valin: Ontario Francophone Judge, 1895 - Prisco, Nestor (Ontario History)

(untitled) (The Ontario Historical Society, 2017)
After Confederation, the provinces administered justice but the dominion government appointed judges. In 1894 Ontario’s Mowat government passed legislation to create Nipissing judicial district. It was then up to the Dominion government to appoint a judge. By early 1895, the Bowell administration issued an order-in-council and the new judge was waiting in the wings. But the perfunctory Royal assent never occurred. Bowell reneged. In a matter of days, the Premier abruptly reversed course and appointed someone else. What grounds may have precipitated such an unusual change of position? Was it partisan pressure, fresh revelations, a response to a crisis or political strategy? Was it a bold move that signaled a new direction? Or was it a balm to quiet unrest or a need to satisfy aggrieved followers and gain support? Those are challenging questions that will be canvassed in this article.